2003
DOI: 10.1002/aheh.200300486
|View full text |Cite
|
Sign up to set email alerts
|

Induced Calcite Precipitation by Cyanobacterium Synechococcus

Abstract: This study investigated the role of the solution composition on calcite precipitation induced by cyanobacteria. The precipitation of calcium carbonate was induced by addition of cyanobacterium cells Synechococcus strain PCC 7942 in two artificial solutions with a different composition at similar saturation states in respect to calcite. Ion-selective electrodes for pH, Ca 2+ , and CO 3 2-monitored the experiments, and the morphology of precipitated crystals was analysed by scanning electron microscopy. The calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 20 publications
2
44
0
Order By: Relevance
“…In fact, calcite precipitation induced by primary production is a common, well known feature in alkaline hard-water lakes (Stabel 1986;Dittrich et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, calcite precipitation induced by primary production is a common, well known feature in alkaline hard-water lakes (Stabel 1986;Dittrich et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…(11,18), and the specific relationship between various environmental factors, such as temperature and pH conditions, on photosynthesis-induced calcification of cyanobacterial biofilms have not, thus far, been investigated. Temperature changes may alter the rate of abiotic degassing and the rate of biological processes and, hence, precipitation.…”
mentioning
confidence: 99%
“…Various studies in recent years have demonstrated the direct effects of carbonate chemistry shift over the course of 5 cyanobacteria growth (Dittrich et al, 2003;Kranz et al, 2010;Millo et al, 2012;Obst et al, 2009b;Yang et al, 2016). In cases where photosynthesis occurred, it results in the stimulation of cell division and DIC uptake, but no alkalinity changes because no other sources of base are added as follows:…”
Section: Carbonate Chemistry Influenced By Viral Lysis Of Cyanobacteriamentioning
confidence: 99%